A Performance Improvement Project to Improve Hand-off Communication Documentation within the Surgical Services Department - Bobbie J. Wich; Millie Escalona; Judith E. Bowling; Ana L. Santos (Library & Knowledge Services and Nursing & Health Sciences Research Departments, 2021)
Over 80% of adverse events in healthcare are due to miscommunication. To improve patient safety, The Joint Commission recommended the use of standardized hand-off communication tools in 2012. One acute care hospital in Southeast Florida implemented standardized handoff reports in 2014 with few revisions since that time. The COVID-19 pandemic brought to light additional critical information was needed to keep patients and staff safe, such as laboratory results indicating the need for isolation precautions. The nurses within the surgical services noticed this critical information was not sufficiently included in the handoff report. The lack of this information led to unnecessary staff exposures and delays in treatment. The quality improvement nurse noticed a significant drop in the use of the standardized hand-off report form used during this time. This drop in compliance lead to concerns for patient and staff safety. The purpose of this performance improvement project was to improve the quality of handoff reports as measured by the level of documentation using the standardized handoff report. The project followed the Plan-Do-Check-Act model for performance improvement, monitoring documentation compliance and reporting the results to the leaders and staff. The handoff report form was revised with input from the staff, resulting in improved efficiency. The nurses' level of satisfaction with the form improved resulting in improved compliance and reducing miscommunications.